2020
DOI: 10.5863/1551-6776-25.7.629
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin for Antibacterial Prophylaxis in Pediatric Patients With Acute Myeloid Leukemia or Undergoing Hematopoietic Stem Cell Transplantation

Abstract: OBJECTIVE This study aimed to evaluate the use of levofloxacin for the prevention of bacterial infections in pediatric patients with acute myeloid leukemia or those undergoing hematopoietic stem cell transplantation. METHODS This study was a single-center, retrospective review designed to assess the frequency of bacteremia with levofloxacin prophylaxis compared with historical controls that used other, clinician-directed antibacterial prophylaxis. The primary outcome of the study was microbiologically document… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The administration of LIIC has been shown to significantly increase the chances of survival in people with AML who are either too old or have other health problems that prevent them from receiving high-dose therapies [ 1 , [5] , [6] , [7] , [8] , [9] , [10] ]. However, getting infections while taking LITR can be a problem, which could make the survival benefits of these drugs less effective [ 3 , 12 , [18] , [19] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of LIIC has been shown to significantly increase the chances of survival in people with AML who are either too old or have other health problems that prevent them from receiving high-dose therapies [ 1 , [5] , [6] , [7] , [8] , [9] , [10] ]. However, getting infections while taking LITR can be a problem, which could make the survival benefits of these drugs less effective [ 3 , 12 , [18] , [19] , [20] , [21] , [22] , [23] , [24] ].…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of complete remission after receiving HIIC lies between 39 and 65% [ 5 ]. Patients acquiring complete remission and not undergoing consolidating therapies have an increased risk of mortality [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies revealed a decrease in the incidence of bacteremia in patients taking levofloxacin compared to other prophylaxis or placebo [ 31 , 32 ]. However, in the pediatric population, the literature presents no differences in the incidence of bacteremia between the group treated with levofloxacin and other prophylaxis, such as cefepime with or without vancomycin or no prophylaxis [ 5 , 20 , 22 ]. The study conducted by Alexander et al proved a reduction in the incidence of bacteremia in children with acute myeloid leukemia receiving levofloxacin prophylaxis compared to the control group without prophylaxis (21.9% vs. 43.4%, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Bloodstream infections (BSI) are frequent and life-threatening complications in HSCT recipients, particularly during pre-engraftment [ 2 , 3 , 4 ]. The incidence of BSI in pediatric HSCT recipients is reported, in the literature, between 20% and 44% [ 5 ]. Approximately 40% of all BSI are related to at least one adverse outcome, constituting a significant burden to the pediatric HSCT population [ 6 ].…”
Section: Introductionmentioning
confidence: 99%